A high performance CsPbBr3 microwire based photodetector boosted by coupling plasmonic and piezo-phototronic effects. (July 2021) - Yang, Zheng; Jiang, Mingming; Guo, Linjuan; Hu, Guofeng; Gu, Yansong; Xi, Jianguo; Huo, Zhihao; Li, Fangtao; Wang, Shufang; Pan, Caofeng
Abstract: Lead halide perovskites have attracted much attention in photodetector fabrication. Up to now, several strategies have been used to modulate the device performance. Here, P3HT-CsPbBr3 monocrystalline microwires based photodetectors are demonstrated by coupling LSPR and piezo-phototronic eﬀects. The photocurrent, response speed and recovery speed under 532 nm laser illumination were increased to nearly 3.5, 70 and 8.4 times when decorated with Au NCs and applied with a compressive strain of −0.29%, respectively. The enhancement of performances can be attributed to the increased light absorption caused by LSPR effect and the enhanced separation of photo-generated holes at the heterojunction interface caused by piezo-phototronic eﬀect. This work suggests that all-inorganic perovskites CsPbBr3 based photodetectors can be significantly enhanced by coupling plasmonic and piezo-phototronic effects. This strategy can be used to modulate the performance of optoelectronic devices based on other piezoelectric materials. Graphical Abstract: P3HT-CsPbBr3 monocrystalline microwires based photodetectors are demonstrated. The photocurrent, response speed and recovery speed were increased to nearly 3.5, 70 and 8.4 times when decorated with Au NCs and applied with a compressive strain of −0.29%, respectively. The enhancement of performances can be attributed to the increased light absorption caused by LSPR effect and the enhanced separation of photo-generated holes at the heterojunction interface caused by piezo-phototronic eﬀect. ga1 Highlights: By utilizing LSPR effect, the responsivity and response/recovery speed of photodetectors were obviously enhanced. The piezo-phototronic effect of CsPbBr3 MWs on devices' performances with different directions and strains were studied. High performance photodetectors based on plasmonic and piezo-phototronic coupling effects were developed.